Nature, environment and culture in East Asia: the challenge of climate change - Meinert, Carmen (Climate and culture 2213-0519, 2013)
Nature, Environment and Culture in East Asia. The Challenge of Climate Change explores East Asian cultural variations in approaching and solving environmental challenges in the past, present, and future-important perspectives from cultural studies to the current global environmental and climate crisis